2018
DOI: 10.1002/leap.1186
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for publishing in English journals: A study of the perceptions of Iranian scholars

Abstract: One of the difficulties in scholarly publishing in English scientific journals is the complex process of revision, which often involves reconstruction of the content and the language of the manuscript and becomes particularly difficult when it comes to non-native writers of English. Focusing mainly on the role of English and language editing in revision, the present study investigated this process in terms of the Iranian scholars' perceptions, problems, and strategies. To this end, 15 Iranian scholars from dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…The trend of previous research shows that writing for publication is widely seen as an academic responsibility and commitment to all countries and higher education institutions. The countries mentioned are China, Taiwan, Iran, Egypt, Korea, USA, Hong Kong, and Poland (Turmudi et al, 2020b;Zheng & Guo, 2019;Chien, 2019;Maniati & Jalilifar, 2018;Shehata & Eldakar, 2018;Kim, 2018). Producing articles for publication fulfils a dual purpose by functioning as students evaluation as well as a duty and means of career progression for Teacher Educator Authors (TEAs).…”
Section: Research Papersmentioning
confidence: 99%
“…The trend of previous research shows that writing for publication is widely seen as an academic responsibility and commitment to all countries and higher education institutions. The countries mentioned are China, Taiwan, Iran, Egypt, Korea, USA, Hong Kong, and Poland (Turmudi et al, 2020b;Zheng & Guo, 2019;Chien, 2019;Maniati & Jalilifar, 2018;Shehata & Eldakar, 2018;Kim, 2018). Producing articles for publication fulfils a dual purpose by functioning as students evaluation as well as a duty and means of career progression for Teacher Educator Authors (TEAs).…”
Section: Research Papersmentioning
confidence: 99%
“…John (1987), Uzuner's (2008) review alone cites 39 research articles (henceforth: RAs) which met her criteria, which include that it must be an empirical study, meaning some other related studies are not included. After the publication of this review (2008), there have been many more studies reported focusing on different countries, for example, Mainland China (Mu, 2019), Taiwan (Chien, 2019), India (Lahiri, 2011), Iran (Maniati & Jalilifar, 2018), Poland (Lopaciuk-Gonczaryk, 2016) and Sudan (Elmalik & Nesi, 2008). Due to limited space, it is impossible to review them all.…”
Section: Literature Reviewmentioning
confidence: 99%
“…To improve the language of their manuscripts, many EAL scholars have turned to fee‐paying ‘literacy brokers’ (Bowker & Ciro, 2019)—a term first coined by Lillis and Curry (2010) to refer to such helpers as translators, proofreaders or editors in the process of publication—or ‘text mediators’ (Luo & Hyland, 2016, 2019), which is similar to ‘literacy brokers’ in denotation but can be either fee‐paying or free. Some have sought convenience editing services from supervisors and colleagues (Luo & Hyland, 2021; Maniati & Jalilifar, 2018; Zeinolabedini & Gholami, 2016) or cooperated extensively with supervisors, colleagues or even students able to improve the language as coauthors (Mu, 2020). Imitation, especially language‐reuse or the use of formulaic sequences has also been a common technique used by EAL scholars in the process of writing or revising manuscripts (Abbas et al, 2020; Flowerdew & Li, 2007; Li, 2005; Mu, 2020).…”
Section: Introductionmentioning
confidence: 99%